The Effect of Position Promotion and Competency on Employee Performance in The Secretariat of West Sulawesi Province - Arismunandar; Ansar; Malik, Tajuddin (Cendekiawan Indonesia Timur, 2022)
Every organization needs to manage human resources well because the key to success is the superiority of tools and technology. In addition, the human factor is a significant resource. Work discipline is a management activity to carry out organizational standards. Employees must know their work discipline because each individual better understands their work. The approach used in this study is qualitative. The type of research used by the researcher is a qualitative descriptive type which studies the existing problems and the applicable working procedures. Qualitative descriptive research aims to obtain information about the existing situation. Data collection techniques are a method that is independent of the analysis method and or even becomes the primary tool of data analysis methods and techniques. There are three stages of activity in analyzing qualitative data: data reduction, data presentation, and drawing conclusions. Employee performance is the results employees achieve in specific functions and tasks to meet job requirements. Parts of a process or activity that are done by employees affect how well they do their jobs. The result is the level at which the employee finishes the work based on the conditions that were given. Many factors can affect the performance of individual employees, namely their abilities, motivation, support received, the work they do, and their relationship with the organization. Employee performance is the result of the synergy of several factors.